Effects of postharvest abiotic stress on the accumulation of bioactive compounds - De la Asunción-Romero, Ruth (2024)
Introduction. Abiotic stress in plants has been studied for many years from agricultural and physiological perspective, generating interest in its application during postharvest stages to induce desirable changes as a basis for the development of functional foods. Objective. To investigate and synthesize information related to the application of postharvest abiotic stress treatments in fruits and vegetables in order to evaluate their impact on the bioactive compounds content. Development. This review was developed in Costa Rica from March 2023 to January 2024 and describes the main effects of applying controlled abiotic stress during postharvest. The includes physical damage, exposure to high or low temperature, application of chemical substances, and irradiation in fruits and vegetables, with special attention to the accumulation of bioactive compounds generated as defense substances or through secondary metabolism. Conclusions. The available information suggests an effect on the accumulation of bioactive compounds, the sensory and general quality of the product, the type of treatment used, and storage conditions. The application of treatments to induce controlled abiotic stress should consider the intensity of stress, as excessive levels hinder subsequent use of the material as raw input for developing functional foods. Therefore, studies on treatments that allows important accumulation of compounds of interest in a specific product, suitable for the use as an raw material in functional food development, should also adedess their effects on relevant quality aspects. Aditionally, the effects of time and storage conditions on the concentration and stability of these compounds should be considered.